OPTIMASI EMULGEL MINYAK ATSIRI ADAS (Foeniculum vulgare Mill.) SEBAGAI ANTI JERAWAT - A, Nurrahman; Pamudji W , Gunawan; Diyah Ikasari, Endang (Media Farmasi Indonesia, 2021)
Acne is a common skin problem. One factor that causes acne is the bacterium Propionibacterium acnes by infecting the skin, causing inflammation. Fennel essential oil (Foeniculum vulgare Mill.) Has potential as an antibacterial. This study aims to determine the combination effect of HPMC, propylene glycol and tween 80 which is formulated to be the optimum preparation of fennel essential oil emulgel with good stability as an anti-acne. Oleum Foeniculi are identified by GC-MS to determine the content of chemical compounds and are tested in vitro against Propionibacterium acnes to find out the minimum inhibitory concentration (MIC). Formula optimization is carried out using the factorial design method. The results showed that Foeniculum oil has content of Benzene, 1-methoxy-4- (2-propenyl) (83.64%), 1-Limonene (3.75%) and Fechone (3.58%) which have potential antibacterial properties against Propionibacterium acnes. Foeniculum oil with a concentration of 6% shows a MIC value of 1.7 cm. The concentration of fennel essential oil is formulated into an optimum emulgel preparation with a combination of 4% : 10% : 10.99%. of HPMC, propylene glycol, and tween 80